The Position of Customary Law in the Legal System: An ExplorationRole, Challenges, and Integration in the Context of National Legal Development - Fitri Arianti Saputri (Journal of Adat Recht, 2024)
This article delves into the role of customary law within the Indonesian legal framework, examining its interaction with the Indonesian Constitution and national laws, and how it influences its application in various domains. Through analytical exploration, several key insights emerge. Firstly, customary law occupies a position in the Indonesian legal hierarchy akin to other national laws, albeit differing in its oral or unwritten nature. Secondly, the Constitution of 1945 acknowledges both written and unwritten laws, including customary law (hukum adat), alongside each other, though it places greater emphasis on formal written legislation in governing societal affairs. Thirdly, parliamentary responsiveness to this dynamic is essential, particularly evident in the creation of regional laws (Qanun) in Aceh, designed to accommodate the evolving nature of customary law within local communities. This adaptability underscores customary law's status as a form of living law, reflective of community norms and practices. Finally, the judiciary plays a pivotal role in overseeing legal consciousness within communities, particularly in addressing legal issues stemming from customary practices. Judicial prudence emerges as a vital source of legal identity, guiding decision-making processes with an understanding of community values and norms.